“Unveiling Unique Pathologies in Obstructive Sleep Apnea: Two Intriguing Case Reports” - Baptista, Peter M.; O'connor, Carlos; Altoron, Mahran; Rodriguez-Alcala, Laura; Plaza-Mayor, Guillermo (Sleep Science, 2024)
Obstructive sleep apnea (OSA) is often associated with reduced pharyngeal muscle tone and an anatomically narrowed pharyngeal airspace. We try to describe two cases with OSA that were diagnosed with vascular lesions during DISE: One of them was an aberrant internal carotid artery, and the second one was a glomus tumor. These anatomic anomalies contribute to airspace narrowing in these patients. These two cases describe an exciting presentation of sleep apnea and remind us of the importance of clinically recognizing vascular alterations to avoid damage during routine oropharyngeal procedures.
Keywords: drug-induced sleep endoscopy; obstructive sleep apnea; glomus tumor; aberrant internal carotid artery